Codeswitching among Trilingual Maghreb International Students: Maghreb-Arabic, French, English - Awawdeh, Ahmad (Center of Language and Cultural Studies [CLCS], 2024)
This article reports on a study of the codeswitches produced by three Maghreb Arabic-French-English adult speakers in their informal conversation. The corpus of the data consists of natural data collected by means of audio-recording. The researcher undertook a quantitative analysis of the participants’ codeswitches to examine the frequency, patterns and linguistic combinations of these codeswitches. The findings revealed that participants engaged in multilingual communication, with a preference for Maghreb Arabic, though they demonstrated proficiency in French and English. While CS occurred at varying rates among participants, the study identified diverse and complex CS patterns, including both intrasentential and intersentential switches. Notably, participants frequently alternated languages within their turns, with the majority of switches occurring between Maghreb Arabic and French, as well as Maghreb Arabic and English. However, about 12.7% of intrasentential switches involved all three languages. This study offers trilingual data that researchers can use for comparative analyses and reference in their own investigations.